1982
DOI: 10.1073/pnas.79.20.6201
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay for components regulating eukaryotic gene expression: a chromosomal factor involved in the generation of histone mRNA 3' termini.

Abstract: We have adapted the oocyte injection procedure for the detection of regulatory components involved in the transcription ofa eukaryotic mRNA gene. Injection of the histone gene repeat h22 DNA ofPsammechinu miliaris into the Xenopwa oocyte nucleus results in correct initiation of the histone mRNAs, but readthrough by RNA polymerase occurs at the 3' end of the H3 histone gene (Hentschel, C. C., Probst, E. & Birnstiel, M. L. (1980) Nature (London) 288, 100-102). Coinjection into the oocyte of a chromosomal salt wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…2, lane c). To exclude the possibility that we had measured a U7 small nuclear ribonucleoprotein-induced increase in mRNA processing (8) and hence of mRNA stability, we analyzed the H2B- stimulating fraction for U7 activity using the H3 processing assay (27). The result of this experiment was negative (data not shown).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2, lane c). To exclude the possibility that we had measured a U7 small nuclear ribonucleoprotein-induced increase in mRNA processing (8) and hence of mRNA stability, we analyzed the H2B- stimulating fraction for U7 activity using the H3 processing assay (27). The result of this experiment was negative (data not shown).…”
Section: Resultsmentioning
confidence: 96%
“…It has also been demonstrated that the frog oocyte shows certain lesions in the transcription of sea urchin histone genes and in the processing of histone mRNA precursors (23). Faulty processing can be overcome by coinjection of chromatin-derived fractions obtained from sea urchin embryos (27). This experimental approach has allowed the isolation and characterization of a novel U7 small nuclear ribonucleoprotein which contains sequence complementarities to histone mRNA precursors and is involved in the generation of correct 3' termini of histone mRNAs (8,26).…”
mentioning
confidence: 99%
“…This approach has been used successfully to identify DNA sequences required for efficient transcription of the herpes simplex virus thymidine kinase gene (25). However, except for the elegant studies of 5S gene transcription (7,8) and a study that describes a chromosomal factor involved in transcription termination of a sea urchin histone gene (41), oocytes …”
Section: -O-acetyltransferase (Cat)mentioning
confidence: 99%
“…Coinjection of DNA and cell extracts into frog oocytes has previously been used in the identification of regulatory factors for sea urchin histone genes (5,12,20) and in transcriptional studies with the adenovirus ElA protein (7,15).…”
mentioning
confidence: 99%
“…Chromatin salt-wash fractions (CSWFs) were isolated from a chicken erythroid cell line by the methods of Stunnenberg and Birnstiel (20). The cells used (ts34 AEV LSCC HD3 [2]) (AEV cells) are transformed by a temperature-sensitive avian erythroblastosis virus, and they express H5 mRNA and protein (19).…”
mentioning
confidence: 99%